Pengaruh Literasi Digital dan Konformitas Teman Sebaya terhadap Cara Berpikir Kritis Siswa Kelas X di SMKN 31 Jakarta - Rahmalika Putri Anjani; Puji Wahono; Muhammad Ikhwan (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2026)
This study aims to determine the effect of digital literacy and peer conformity on the critical thinking of grade X students at SMKN 31 Jakarta. The study used a quantitative method with a survey approach. The study population was 217 students, while the research sample was 141 respondents obtained using the Slovin formula. The data collection technique was carried out by distributing questionnaires using a Likert scale. Data were analyzed using the Structural Equation Modeling-Partial Least Square (SEM-PLS) method with the help of the SmartPLS application. The results showed that digital literacy had a positive and significant effect on students' critical thinking. This was evidenced by the path coefficient value of 0.436, the T-statistic value of 6.988, and the P-value of 0.000. Peer conformity also had a positive and significant effect on students' critical thinking with a path coefficient value of 0.447, the T-statistic value of 7.290, and the P-value of 0.000. Furthermore, the R-square test results obtained a value of 0.445, indicating that digital literacy and peer conformity variables were able to explain 44.5% of the critical thinking variable, while the remaining 55.5% was influenced by other factors outside the study. Based on these results, it can be concluded that digital literacy and peer conformity have a positive and significant influence on the critical thinking of 10th-grade students at SMKN 31 Jakarta.